An effective pre-treatment method for eliminating interference by serum albumin for analysis of anti-rHSA antibodies. Issue 9 (9th February 2023) - Sun, Yunjuan; Xu, Jingzhi; Xie, Xinyao; Song, Haifeng
Abstract : Analysis of anti-drug antibodies (ADAs) is important for risk assessment in clinical trials. Abstract : Analysis of anti-drug antibodies (ADAs) is important for risk assessment in clinical trials. ADA detection can be very difficult in the presence of high circulating levels of drugs or target proteins. We present an effective pretreatment method for eliminating interference by endogenous albumin for analyses of recombinant human serum albumin (rHSA) ADAs. Polyethylene glycol (PEG) precipitation was used to extract albumin–ADA immune complexes from serum samples. Following acid dissociation, albumin-reactive antibodies could be detected through an electrochemiluminescence (ECL) method. Normal human serum was used to establish detectable cut points. Goat anti-human albumin was used as the positive control to evaluate the assay performance. With regard to detection of anti-HSA antibodies, pretreatment with PEG could reduce the interference from albumin in serum. We discovered that the optimized PEG precipitation and acid dissociation (PandA) method had good performance in terms of sensitivity, drug tolerance, and selectivity.